2020
DOI: 10.1002/er.5225
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning–based optimization for hydrogen purification performance of layered bed pressure swing adsorption

Abstract: Summary An adsorption, heat and mass transfer model for the five‐component gas from coal gas (H2/CO2/CH4/CO/N2 = 38/50/1/1/10 vol%) in a layered bed packed with activated carbon and zeolite was established by Aspen Adsorption software. Compared with published experimental results, the hydrogen purification performance by pressure swing adsorption (PSA) in a layered bed was numerically studied. The results show that there is a contradiction between the hydrogen purity and recovery, so the multi‐objective optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…Studies have shown that ANN models can predict hydrogen purification performance well [36]. The ANN method uses simple mapping to approximate and implement a certain function of complex mapping.…”
Section: Optimization Of Hydrogen Purification Performance Based On Interior Point Methodsmentioning
confidence: 99%
“…Studies have shown that ANN models can predict hydrogen purification performance well [36]. The ANN method uses simple mapping to approximate and implement a certain function of complex mapping.…”
Section: Optimization Of Hydrogen Purification Performance Based On Interior Point Methodsmentioning
confidence: 99%
“…The PSA optimisation using neural networks was ten times faster as compared to using high-fidelity simulations for functional evaluations. Instead of constructing a surrogate model for each performance indicator, Xiao et al 131 used a multi-output feed-forward neural network architecture to predict purity, recovery and productivity in the PSA optimisations. Vo et al 132 formulated an integrated process model based on the combination of different feed-forward neural networks, which represent the input-output mapping structure of cryogenic, membrane and PSA units for hydrogen recovery and CO 2 capture from the tail gas of SMR-based hydrogen plants.…”
Section: Process Modelling and Optimisationmentioning
confidence: 99%
“…As a result, the relative error of Pareto solutions in both objectives was less than 1% and accelerated the optimization routine by ten times. Xiao et al 15 instead used a multi-output feed-forward ANN architecture to predict process performances in the PSA optimizations. Pai et al 16 extended the use of feed-forward ANN models to predict the axial profiles of the intensive variables for a four-step VSA process at CSS, and the models were experimentally validated.…”
Section: Introductionmentioning
confidence: 99%